2014
DOI: 10.1245/s10434-014-3851-y
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor, Progesterone Receptor, and HER2 Status Predict Lymphovascular Invasion and Lymph Node Involvement

Abstract: Background The ACOSOG Z0011 trial demonstrated that axillary dissection (ALND) is not necessary for local control or survival in women with T1/2cN0 cancer undergoing breast-conserving therapy. There is concern about applying these results to triple-negative (TN) cancers secondary to their high local-recurrence (LR) rate. We examined the frequency of lymphovascular invasion (LVI) and nodal metastases in TN cancers to determine whether ALND can be safely avoided in this subtype. Methods Data were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
5
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 38 publications
5
41
5
4
Order By: Relevance
“…This supports previous evidence from different studies in which patients with these tumor types did not show differences in axillary cancer burden although presenting a greater risk of recurrence and poor prognosis [22,23]. Therefore, these patients should not be excluded from being given the option of avoiding ALND.…”
Section: Discussionsupporting
confidence: 88%
“…This supports previous evidence from different studies in which patients with these tumor types did not show differences in axillary cancer burden although presenting a greater risk of recurrence and poor prognosis [22,23]. Therefore, these patients should not be excluded from being given the option of avoiding ALND.…”
Section: Discussionsupporting
confidence: 88%
“…Detection of LVI in the primary tumour is a marker of metastatic potential. The prognostic value of LVI has been demonstrated by several independent studies [6,7,8,9,10,11,12,13,14]. In a previous study of 3,812 cases of BC [7], it has been demonstrated that LVI is not only an independent prognostic variable in the whole series but also in the various prognostic subgroups, including the lymph node-negative cohort.…”
Section: Introductionmentioning
confidence: 93%
“…There is also a correlation between LVI and BC molecular subtype. Triple-negative or basal-like molecular classes showed the least association with LVI despite their poor prognosis and higher tendency to local recurrence [10]. Contrasting this, luminal and HER2-positive classes showed the highest incidence of LVI.…”
Section: Tumour Histological Features and LVImentioning
confidence: 99%
“…Triple-negative breast tumors, however, have the lowest risk of high-volume nodal involvement of all molecular subtypes [26]. It is a significant clinical question whether specific subtypes may need differential consideration when deciding on axillary management in pN1(sn) cases.…”
Section: What Is the Best Management Of Cn0pn1(sn) Breast Cancer Patimentioning
confidence: 99%